A Comparison of Two Botanical Pyrethrum Synergists from Ocimum kilimandscharicum and Tagetes minuta in the Control of Malaria Vector the Anopheles gambiae - Ondigo , Rachel A.; Sum , Kefa; Ndalut , Paul K.; Muthoka, Titus M. (African Journal of Education,Science and Technology (AJEST), 2015)
Mosquitoes are general vectors that carry disease-causing viruses and parasites from person to person. Some of these diseases can be life threatening such as dengue, malaria, rift valley fever, yellow fever among others. Vector control is by far one of the most successful methods for reducing the incidences of diseases. However, the emergence of wide spread insecticide resistance and the potential environmental concern associated with some synthetic insecticides has indicated that additional approaches to control the proliferation of mosquito population would be an urgent research area. Concern to quality and safety of life in controlling mosquito, has shifted steadily from the use of conventional chemicals toward alternative insecticides that are target-specific, biodegradable, environmentally safe, and botanicals in origin. Pyrethrins are natural plant compounds used in commercial vector control. They are usually formulated with synergist to improve quality of insecticide, increase its efficacy, fight resistance and make it cost effective; thus, necessitating the need to explore more on natural synergists. In this study, the essential oils from Ocimum kilimandscharicum and Tagetes minuta flowers were extracted by steam distillation. Crude extracts was used to conduct a bioassay for larvicidal and adulticidal activity against 4th instars An. Gambiae larvae. For the bioassay, six concentrations (10ppm,20ppm 30ppm and 40ppm) each with 3 replicates, with a final total number of 60 larvae for each concentration. For each concentration of oil solution twenty 4th instars larvae were inserted. Mortalities were recorded after 1, 3, 6, 9, 12 and 24hours exposure, during which no food was offered to the larvae. Each batch of replicates contained distilled water (negative control) pyrethrins (as positive control) and 1% DMSO at the same concentrations as the test solution as standards. Bioassays provided LC50 and LC90 values for the synergist mixtures. For O. kilim and scharicum the values were 0.0076 and 0.00167ml while for T. minuta it was 0.00361and 0.01644ml respectively. Data was evaluated by a regression and probit analysis. The active ingredients in the essential oils as separated and identified by GC-MS are with the author. This tests will enable author and other researchers identify the most active component of the synergist to enable any further large production be done in the future.